Drought tolerance in selected aerobic and upland rice varieties is driven by different metabolic and antioxidative responses - Melandri, Giovanni; AbdElgawad, Hamada; Floková, Kristýna; Jamar, Diaan C; Asard, Han; Beemster, Gerrit T S; Ruyter-Spira, Carolien; Bouwmeester, Harro J (Planta, 2021)
Sugar-mediated osmotic acclimation and a strong antioxidative response reduce drought-induced biomass loss at the vegetative stage in rice. A clear understanding of the physiological and biochemical adaptations to water limitation in upland and aerobic rice can help to identify the mechanisms underlying their tolerance to low water availability. In this study, three indica rice varieties-IR64 (lowland), Apo (aerobic), and UPL Ri-7 (upland)-, that are characterized by contrasting levels of drought tolerance, were exposed to drought at the vegetative stage. Drought-induced changes in biomass, leaf metabolites and oxidative stress markers/enzyme activities were analyzed in each variety at multiple time points. The two drought-tolerant varieties, Apo and UPL Ri-7 displayed a reduced water use in contrast to the susceptible variety IR64 that displayed high water consumption and consequent strong leaf dehydration upon drought treatment. A sugar-mediated osmotic acclimation in UPL Ri-7 and a strong antioxidative response in Apo were both effective in limiting the drought-induced biomass loss in these two varieties, while biomass loss was high in IR64, also after recovery. A qualitative comparison of these results with the ones of a similar experiment conducted in the field at the reproductive stage showed that only Apo, which also in this stage showed the highest antioxidant power, was able to maintain a stable grain yield under stress. Our results show that different metabolic and antioxidant adaptations confer drought tolerance to aerobic and upland rice varieties in the vegetative stage. The effectiveness of these adaptations differs between developmental stages. Unraveling the genetic control of these mechanisms might be exploited in breeding for new rice varieties adapted to water-limited environments.
Keywords: antioxidancia; období sucha; Drought; Oryza sativa; rýže (rod); Metabolism; šlechtění rostlin; Osmotic adjustment; Oryza; Plant Breeding; Biomass; Antioxidative response; Antioxidants; Droughts; Vegetative stage; fyziologická adaptace; Adaptation, Physiological